Morte e vida Severina: o suicídio como possibilidade posta socialmente - Aline Fábia Guerra de Moraes (2019)
The discussion about death in today's society is accompanied by social constraints that are explicit at times, and then seem to disappear. One of these restrictions specifically concerns self-murder, suicide, because the finitude the act reveals and the conditions that lead one to this 'desperate action' bother society. This annoyance is indirectly reflected in studies on the subject, which mostly remain in the appearance of the phenomenon, associating suicide with illness and blaming the individual who takes his own life. In this sense, we seek to escape from this idea of suicide linked only to the bodily imbalance and defend the thesis that the elements that produce suicide as an alternative to the individual are engendered in the capitalist mode of production through the work process' organization. To this end, we choose a critical position, which drinks from, but does not dive into Marx's historical dialectical materialism, in order to find the essence of the suicide phenomenon and escape the appearance that is commonly absorbed in works about this subject. However, it is necessary to start from this appearance and, therefore, we have analyzed official publications of the World Health Organization; suicide reports available on electronic portals; and semi-structured interviews with individuals directly or indirectly involved with suicide (professionals, people who tried or almost came to terms with suicide and suicidal relatives). The reflections on the phenomenon in question have shown that what is decisive in the analysis that we propose to do is not the efficiency of the act itself, that is, the individual having managed to die or not, but the very fact that suicide emerges as a social possibility for this person. And this possibility reflects the ways in which social relations are organized, these blame the individual who chooses for such an alternative, rather than pointing to the relations that have produced this option, for exposing suicide as its essence in capitalist society is to expose the adversities of this society, is to expose the 'severina life'. Thus, we conclude that the movement that capital makes in the midst of the need for production, competitiveness, rivalry, proves to be the best among the rest, and so on, makes suicide a concrete possibility for the individual, something that can be chosen as a way to exterminate the pain that is felt, pain caused by the movement of capital itself.